Attitudes of Clinicians about Screening Head and Neck Cancer Survivors for Lung Cancer Using Low-Dose Computed Tomography. (January 2020) - Dukes, Kimberly; Seaman, Aaron T.; Hoffman, Richard M.; Christensen, Alan J.; Kendell, Nicholas; Sussman, Andrew L.; Vélez-Bermúdez, Miriam; Volk, Robert J.; Pagedar, Nitin A.
Objective: National guidelines recommend lung cancer screening (LCS) using low-dose computed tomography (LDCT) for high-risk patients, including survivors of other tobacco-related cancers like head and neck cancer (HNC). This qualitative study investigated clinicians' practices and attitudes toward LCS with LDCT with patients who have survived HNC, in the context of mandated requirements for shared decision making (SDM) using decision aids. Methods: Thematic analysis of transcribed semi-structured clinician interviews and focus group. Results: Clinicians recognized LCS' utility for some HNC survivors with smoking histories. However, they identified many challenges to SDM in diverse clinic settings, including time, workflow, uncertainty about guidelines and reimbursement, decision aids, competing patient priorities, unclear evidence, potentially heightened patient receptivity and stress, and the complexity of discussions. They also identified challenges to LCS implementation. Conclusions: While clinicians feel that LDCT LCS may benefit some HNC survivors, there are barriers both to implementing LCS SDM for these patients in primary care as currently recommended and to integrating it into cancer clinics. Challenges for SDM across settings include a lack of decision aids tailored to patients with cancer histories. Given recommendations to broaden LCS eligibility criteria, more research may be required before refinement of current guidelines.